Artificial Intelligence Intervention for Digital Literacy and Digital Amnesia Among Islamic Education Students at Universitas Terbuka in Society 5.0 - Frimayanti, Ade Imelda (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
his study examines the impact of Artificial Intelligence (AI) interventions on digital literacy, digital amnesia, and the readiness of Universitas Terbuka (UT) students in the Islamic Education Study Program to face the challenges of the Society 5.0 Era. Using a mixed methods approach with a sequential explanatory case study design, quantitative data from 100 students were analyzed using simple linear regression, while qualitative data were processed inductively. The findings reveal that AI interventions significantly enhance digital literacy by 81% (high category) and reduce digital amnesia by 65.7% (moderate category). AI interventions also prepare students for the Society 5.0 Era through active participation, the use of AI applications, positive interactions with tutors, technology utilization, and student collaboration. The study recommends strengthening technological infrastructure, providing tutor training, and developing AI-based learning materials to optimize learning at UT, enabling students to better face the challenges of the Society 5.0 Era.